Freezing Thermal Cycling Modulation of the Photoelectric Conversion in Organic Metal Halide Perovskites - Shengjian Qin; Jiayu Song; Yinan Jiao; Jiale Meng; Hang Su; Jinjin Zhao (EcoMat, 2025)
ABSTRACT The industrialization of perovskite thin‐film photovoltaics (PVs) has attracted global attention owing to their high photoelectric conversion efficiencies (PCEs). Seasonal temperature cycling significantly impacts the efficiency and stability of these devices, yet this phenomenon remains underexplored. This study investigates the influences of freezing thermal cycling (between near 0°C and 60°C) on the PV performance of traditional methylammonium lead iodide (MAPbI3) perovskite films. The results show that freezing thermal cycling introduces tensile lattice strain along [110] direction in MAPbI3 perovskite films. The sample without thermal cycling exhibits the minimal tensile lattice strain of 0.32%, resulting in a minimal bandgap of 1.588 eV, reduced defect density, and extended carrier lifetime of 33.78 ns. The PV device using this perovskite film as the absorber layer demonstrates a maximum photocurrent of 83 μA. Theoretical calculations confirm that a moderate tensile strain along the [110] direction in tetragonal MAPbI3 phase enhances the photoelectric conversion performance by reducing the bandgap and increasing the formation energy of iodine vacancies. These results highlight freezing thermal cycling as an effective strain engineering strategy offers a scalable approach for tuning photoelectric conversion performance of perovskite‐based devices.